Treatment of Chronic Headache of Cervical Origin With Lipostructure: An Observational Study. Issue 3 (23rd October 2012) - Gaetani, Paolo; Klinger, Marco; Levi, Daniel; Bussone, Gennaro; Giannasi, Silvia; Caviggioli, Fabio; Marazzi, Mario; Broggi, Giovanni
Abstract : Objective.— To test feasibility, safety, and efficacy of local transplant of stromal fraction of adipose tissue in the treatment of chronic headaches of cervical origin. Background.— Chronic headaches of cervical origin (chronic cervicogenic headache and occipital neuralgia) are characterized by persistent pain due to the involvement of the great occipital nerve, with concurrent myofascial spasm and the consequent nerve entrapment within the trapezoid tunnel. Methods.— Tolerability and effectiveness of treatment of chronic cervicogenic headaches refractory to conventional therapies were evaluated in 24 patients. The visual analog scale of pain and the medication use diary were used in the 3 months preceding treatment; moreover, in order to verify the quality of life, patients are required to fill before surgery the Neck Pain Disability Index, the Headache Disability Index, migraine disability assessment scale questionnaire, and the short‐form 12 standard v1 questionnaire. Follow‐up examination was performed at 3 and 6 months. Results.— In 19 cases (79.2%), a good clinical response was recorded. At 6‐month follow‐up analysis, recurrence of occipital pain was recorded in 7 cases (29.2%); there is a significant reduction in disability and pain scores, and also a significant reduction of need for pharmacologic treatment and a fast return to previous work capacities. Conclusions.— The key point of our therapeutic strategy might be the regenerative role of stromal fraction of adipose tissue transplanted in the area of the occipital nerve entrapment; the results of the present study are encouraging both in terms of reduction of pain scores and in terms of quality of life improvement. The technique is minimally invasive, and no complications were recorded; indeed, the procedure seems to be safe and effective, and thus, a randomized study with larger follow‐up and in a large series will be started.